INVESTIGATION OF CONJUGATE HEAT TRANSFER OF A ROTATING LATENT HEAT ENERGY STORAGE - Ali, Zain (IRC, 2016)
Wide application of renewable energy such as wind, solar and tidal are hampered by their intermittent nature, i.e. they are not available all the time. Energy storage system are essential for such sources of energy, as they increase the efficiency of a system by reducing the mismatch between demand and supply. Latent Heat Storage (LHS) is one of the many thermal storage systems, which, when coupled with solar field can be used store thermal energy. However, an issue exists with the its slow heat transfer performance. Numerous research has been conducted, with aims of improving the rate of heat transfer of a LHS system. However, studies related to the rotation of a LHS system in hopes of improving the heat transfer rate are minimum. Therefore, this project is undertaken to study the effect of rotation on a LHS based TES system during its charging and discharging phase. A computational model is developed and validated against experimental counterpart, available in literature. The heat transfer performance of steady and rotating latent heat storage is then evaluated by utilizing the developed model. The results indicate an increase in heat transfer performance of an LHS system with the introduction of rotation which induces more uniform heat transfer.